STRATEGIES AND INNOVATIONS OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN SHAPING THE RELIGIOUS CHARACTER OF STUDENTS AT SMPN 22 SURABAYA - Ermawan, Bintang Tegar Satya; Fahmi, Muhammad; Mas’ud, Ali (Jurnal Kajian Pendidikan dan Psikologi, 2026)
This The formation of religious character in schools faces increasingly complex challenges, particularly due to declining discipline in worship, behavioral changes resulting from the strong influence of social media, and a lack of consistent religious habits in students' daily lives. This condition is also evident at SMPN 22 Surabaya, so Islamic Education (PAI) teachers need to design learning strategies and innovations that not only focus on understanding the material but also accompany and guide students in building better religious habits. This study aims to describe how PAI teachers develop religious character through exemplary behavior, habit formation, learning innovation, and mutually supportive cooperation between school elements. This study uses a descriptive qualitative approach with observation, in-depth interviews, and documentation techniques. Data analysis was conducted using the Miles and Huberman model through a process of reduction, presentation, and conclusion drawing. The results showed that PAI teachers became role models for students in terms of worship, discipline, and daily behavior. Religious habits were successfully instilled through activities such as tadarus, dhuha prayer, congregational zuhr prayer, kultum, and moral habits. Teachers also apply more lively and relevant learning through contextual, reflective, collaborative methods and the use of digital media. In addition, collaboration between teachers, principals, teachers on duty, homeroom teachers, and student council strengthens the entire religious program so that it is more focused and sustainable. However, obstacles were found, such as unstable student discipline, the influence of social media, and limited facilities and time available. The study concluded that the strategies and innovations of PAI teachers contribute significantly to the formation of students' religious character. The implication is that schools need to strengthen religious culture, develop technology-based learning, and expand cooperation among all school members so that character building can be more optimal and sustainable.